2011
DOI: 10.1055/s-0030-1250659
|View full text |Cite
|
Sign up to set email alerts
|

Stage of Action of Naturally Occurring Andrographolides and Their Semisynthetic Analogues against Herpes Simplex Virus Type 1in Vitro

Abstract: Andrographolide, an ENT-labdane diterpene, has been found to have activities against many viruses. Three free hydroxyls at C-3, C-14, and C-19 are involved in the activities. No stage of action has ever been explored. In this study, the naturally occurring compounds of andrographolide, 14-deoxy-11,12-didehydroandrographolide and 14-deoxyandrographolide, and eight semisynthetic analogues, modified at the three free OHs of andrographolide, were explored for their anti-HSV-1 activities. The concentrations that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Andrographolide (Androg) is a bioactive ent- labdane diterpene isolated from Andrographis paniculata Nees, Acanthaceae and has been used to treat various diseases traditionally in the Southeast Asian countries, India and China. The pure form of Androg and its derivatives were isolated and already characterized [ 7 ]. In our recent studies, 3, 19-isopropylideneandrographolide (IPAD), an analogue of Androg, was found to exert an absolute inhibitory effect on HSV-1 post-infection at the concentration of 11.96 μM [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrographolide (Androg) is a bioactive ent- labdane diterpene isolated from Andrographis paniculata Nees, Acanthaceae and has been used to treat various diseases traditionally in the Southeast Asian countries, India and China. The pure form of Androg and its derivatives were isolated and already characterized [ 7 ]. In our recent studies, 3, 19-isopropylideneandrographolide (IPAD), an analogue of Androg, was found to exert an absolute inhibitory effect on HSV-1 post-infection at the concentration of 11.96 μM [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pure form of Androg and its derivatives were isolated and already characterized [ 7 ]. In our recent studies, 3, 19-isopropylideneandrographolide (IPAD), an analogue of Androg, was found to exert an absolute inhibitory effect on HSV-1 post-infection at the concentration of 11.96 μM [ 7 , 8 ]. IPAD affects the early steps of DNA replication in HSV-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has demonstrated that 14-DDA isolated from A. paniculata shows virucidal activity against herpes simplex virus 1 (HSV-1) (25). Our previous study also found that 3 andrographolide analogues, namely 14-acetyl-3,19-isopropylideneandrographolide, 14-acetylandrographolide, and 3,14,19-triacetylandrographolide, significantly exhibit preinfection step activity against HSV-1 and concluded that 14-acetyl analogues are good for blocking viral entry (19). Several natural compounds have been reported to have effects on the early step of HPV infection.…”
Section: Discussionmentioning
confidence: 88%
“…The preparation and structure of A. paniculata compounds have been described previously (19). Andrographolide (Androg), 14-DDA, and IPAD were dissolved in dimethyl sulfoxide (DMSO; Amresco, Solon, OH) for stock solutions (2 mg/mL) and stored at -20 C. The stock solutions were freshly diluted to the indicated concentrations with culture medium before using in experiments.…”
Section: A Paniculata Compoundsmentioning
confidence: 99%